Genotype by Diet Interaction on Body Weight of the Local Chicken and its Crosses with Barred Plymouth Rock - Mmereole, F.U.C.; Udeh, I. (International Journal of Poultry Science, 2009)
In a 2x4 factorial arrangement, the effect of genotype, diet and their interaction on body weight and weight gain of the F1 crosses between the local chicken and Barred Plymouth Rock were investigated. Birds of each genotype were separated into two dietary groups at day old. One group was placed on layer type diets and other on broiler type diet. The body weights and weight gains of the two diet groups were monitored up to 12 weeks of age. The effect of genotype by diet interaction on body weight and weight gain was not significant (p>0.05) throughout the period. Birds on broiler diet regime were significantly (p